Conversion coating technology for recovery and reuse of waste Mg alloy polishing powder. (25th September 2022) - Zhang, Yuyuan; Xu, Kaili; Liu, Bo; Ge, Ji
Abstract: The waste dust from Mg alloy grinding not only has the danger of explosion, but also reduces the performance of Mg due to the oxidation and hydrolysis of Mg, which seriously limits the reuse of Mg alloy waste dust. In order to avoid the oxidation of Mg alloy dust and recycle it, four inerting agents, including sodium citrate and sodium alginate, were selected to inertize waste Mg alloy dust. The results show that when used alone, none of the inerting agents can completely prevent the production of Mg(OH)2 . After the combination of organic sodium citrate and inorganic sodium silicate, the inerting efficiency of Mg alloy dust can reach 99.4%, which is more than 20% higher than that of any inerting agent used alone. XRD and FTIR results showed that a composite conversion film composed of [SC-Mg] and hydrated magnesium silicate is formed on the surface of waste Mg alloy dust particles, which blocks the contact between external water molecules and Mg 2+ ions. Stability test under different conditions showed that the composite conversion film can maintain good stability under different temperatures, disturbance speeds and Cl − concentrations. The inerted Mg alloy dust (0.4 wt% SC+0.2 wt% SS) has been verified in industrial application, and the reuse possibility of residual Mg alloy powder has been confirmed. This study not only provides a simple and effective method for recycling waste Mg alloy dust, but also reduces the explosion risk during dust collection and transportation. Graphical abstract: Image 1 Highlights: Inerting of waste Mg alloy dust by sodium citrate and sodium silicate. The conversion film can completely prevent the oxidative hydrolysis of waste Mg alloy dust. The conversion film showed good stability under different conditions.